PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA - Suryaningsih, Nunuk; Ariesanti, Alia (Universitas Ahmad Dahlan, 2012)
Recent years many companies are increasingly recognizing the importance of implementing a program of corporat social resposibility (CSR) as part of ots business srategy. Intense competition in the business word sometimes makes the company justifies any means to increase profit with lower costs, thus resulting in corporate social responsibility aside. The study was conducted to provide empirical evidence of the influence of CSR on corporate profitability. This study used a sample of 20 companies listed on the Stock Exchange of manufacturing the 2005-2009 period. The research data obtained from annual financial reporting issued by the company each year. Determination of the sample using purposive sampling method. Testing the hypothesis using a simple linear regression analysis. The results show that the disclosure of CSR effect company profitability when viewed using the Return of Equity, but had no effect on Return on Assets and Return on Investment. In addition, the study provides empirical evidence that there are differences in the scope of the disclosure of Corporate Social Responsibility between in periods before and after the enactment of Law No.40 of 2007 regarding Limited Liability Company.